2017
DOI: 10.1371/journal.pone.0170382
|View full text |Cite|
|
Sign up to set email alerts
|

Liver AMP-Activated Protein Kinase Is Unnecessary for Gluconeogenesis but Protects Energy State during Nutrient Deprivation

Abstract: AMPK is an energy sensor that protects cellular energy state by attenuating anabolic and promoting catabolic processes. AMPK signaling is purported to regulate hepatic gluconeogenesis and substrate oxidation; coordination of these processes is vital during nutrient deprivation or pathogenic during overnutrition. Here we directly test hepatic AMPK function in regulating metabolic fluxes that converge to produce glucose and energy in vivo. Flux analysis was applied in mice with a liver-specific deletion of AMPK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 68 publications
(111 reference statements)
6
20
0
Order By: Relevance
“…In contrast, recent work has added to the growing body of literature refuting such a regulatory role for liver AMPK in glucose homeostasis. We recently reported that 15-week-old mice lacking liver AMPK␣1␣2 subunits had no effect on endogenous glucose production or gluconeogenic flux following 7 h of fasting (29).…”
Section: Role Of Hepatic Ampk In Glucose Homeostasis During Exercisementioning
confidence: 98%
See 4 more Smart Citations
“…In contrast, recent work has added to the growing body of literature refuting such a regulatory role for liver AMPK in glucose homeostasis. We recently reported that 15-week-old mice lacking liver AMPK␣1␣2 subunits had no effect on endogenous glucose production or gluconeogenic flux following 7 h of fasting (29).…”
Section: Role Of Hepatic Ampk In Glucose Homeostasis During Exercisementioning
confidence: 98%
“…The 2 H/ 13 C MFA is sufficiently robust to detect an increase in CAC fluxes (V CS and V SDH ) (41). It is important to note that using this methodology, a higher V CS in liver-specific AMPK KO mice compared with WT mice following a 19-h fast was shown (29). Thus, the method is sensitive to experimental and physiological differences in CAC and gluconeogenic fluxes between WT and KO mice.…”
Section: Role Of Hepatic Ampk In Glucose Homeostasis During Exercisementioning
confidence: 98%
See 3 more Smart Citations